Modified nanofiber membrane and treatment method of nickel-tin-containing photovoltaic aluminum profile anodic oxidation wastewater

By chemically modifying the polylactic acid electrospinning film, a modified nanofiber membrane was prepared, which solved the problem that the prior art could not simultaneously remove nickel and tin in sewage efficiently, and achieved an efficient and economical sewage purification effect.

CN119593138AActive Publication Date: 2025-03-11XIAMEN ANTAI NEW ENERGY TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411611988.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-11
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing membrane separation method cannot synchronously and efficiently remove nickel and tin pollutants in sewage, resulting in a low removal rate and cannot meet emission standards.

Method used

By chemically modifying the polylactic acid electrospinning membrane, introducing modifiers such as niobium carbide, vanadium carbide, molybdenum carbide, and a modified nanofiber membrane can be prepared, which can efficiently remove nickel and tin ions in a filtration step.

Benefits of technology

The synchronous and efficient removal of nickel and tin in wastewater is achieved. The nickel removal rate is greater than or equal to 99%, and the tin removal rate is greater than or equal to 98%, which meets emission standards, and is easy to operate in the process and saves labor costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132223070000061
    Figure BDA0005132223070000061
Patent Text Reader

Abstract

The invention relates to a modified nanofiber membrane and a treatment method of nickel-tin-containing photovoltaic aluminum profile anodic oxidation wastewater, and the preparation method of the modified nanofiber membrane comprises the following steps: S1, dispersing polylactic acid into a solvent to obtain a dispersion liquid; s2, adding at least one modifier of niobium carbide, vanadium carbide and molybdenum carbide into the dispersion liquid, and uniformly stirring to obtain a spinning solution; s3, adding the spinning solution into electrostatic spinning equipment, and spinning by utilizing the electrostatic spinning equipment to obtain the modified nanofiber membrane. The modified nanofiber membrane is mounted in a filtering device and has remarkable nickel removal and tin removal effects on nickel-tin-containing photovoltaic aluminum profile anodic oxidation wastewater, the nickel removal rate is larger than or equal to 99%, the tin removal rate is larger than or equal to 98%, synchronous removal of nickel and tin is achieved, the treatment procedure of the anodic oxidation wastewater can be simplified, the treatment cost can be reduced, and the method is suitable for industrial production. The industrial application prospect is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrostatic spinning technology and a wastewater treatment technology, in particular to a method for treating wastewater from anodizing of a modified nanofiber membrane and a nickel-tin-containing photovoltaic aluminum profile. Background Art

[0002] Aluminum profiles used in the photovoltaic field are generally aluminum 6 series alloys, such as 6005, 6061, and 6063 aluminum alloys. This type of alloy material itself does not have special corrosion resistance. Since the environment in which photovoltaic profiles are used has high requirements for the surface of aluminum alloys, these 6 series alloys are often anodized to increase their corrosion resistance during use and extend their service life in certain extreme climates.

[0003] The core of aluminum profile anodizing is to pass electricity through the aluminum profile in a sulfuric acid tank to form a dense anodized film on the surface, and then pass through the coloring tank and sealing tank to make the aluminum profile surface have a specific color and better corrosion resistance and weather resistance. Usually, the total nickel ion content in the coloring tank and sealing tank is 50g / L, and the tin ion content is 40g / L. When the mixed chemical substances in the tank become ineffective due to repeated use, the tank liquid will be replaced, resulting in a lot of waste liquid.

[0004] The purpose of centralized treatment of the wastewater from anodizing of aluminum profiles generated in the above process is mainly to remove heavy metals, which can have serious adverse effects on human life and environmental ecology. For example, nickel and tin can enter the human food chain by infiltrating groundwater resources and being adsorbed by plants, which can cause some troubles to humans, including eczema and allergies, lung cancer and pulmonary fibrosis, chronic bronchitis and sinusitis, heart and liver dysfunction, skin irritation and headaches. According to relevant requirements, the content of tin, nickel, etc. in the treated wastewater should meet the "Electroplating Pollutant Emission Standard" GB21900-2008. Other pollutants such as total aluminum, phosphates, etc. should also meet the national "Comprehensive Standard for Wastewater Emission" GB 8978-1996 before they can be discharged.

[0005] At present, there are many methods to remove heavy metal elements. For example, the chemical precipitation method adds chemical agents to make the wastewater with the same heavy metal ion reach the precipitation pH value of the heavy metal, or adjusts the pH value of the wastewater containing multiple metal ions in stages to form precipitated sludge, and then removes the heavy metal ions in the water by flotation scraping or sedimentation sludge. The coagulation method adds coagulants to make the heavy metal ions in the wastewater condense or flocculate, generate larger particles and precipitate, thereby removing the heavy metals in the wastewater. The adsorption method uses the structure of the adsorbent to remove heavy metal ions, such as activated carbon, silica gel, etc. The ion exchange method uses ion exchangers to separate harmful substances in wastewater. Commonly used ion exchangers include ion exchange resins, zeolites, etc. The membrane separation method uses the selectivity of polymers to separate substances.

[0006] Among the above methods, the membrane separation method has the advantages of not introducing new pollution, being easy and controllable to operate, and being reusable, etc. For example, Chinese patent application CN 109107549 A discloses a method for preparing a nanofiber membrane for adsorbing heavy metal nickel ions in wastewater, and the prepared nanofiber membrane is used to adsorb nickel ions, which has a good effect of removing nickel from wastewater.

[0007] However, tin and nickel have different properties. The adsorption of nickel by nanofiber membranes is the result of weak electrostatic forces between the active groups of nickel and the active groups of the membrane. The chemical properties of tin are different from those of nickel, and tin ions do not have the same active groups as nickel ions. Therefore, nanofiber membranes that have a good adsorption effect on nickel cannot effectively remove tin ions. Studies have found that the nanofiber membranes provided by Chinese patent application CN 109107549 A have a tin ion removal rate of only 5-10%, and cannot simultaneously and efficiently remove nickel and tin pollutants in sewage. Summary of the invention

[0008] The purpose of the present invention is to overcome the problem that the existing membrane separation method cannot simultaneously and efficiently remove nickel and tin pollutants in sewage, and to provide a method for treating anodized wastewater of a modified nanofiber membrane and a nickel-tin-containing photovoltaic aluminum profile.

[0009] The inventor believes that, based on the consideration of saving process and economic cost, removing nickel and tin ions in one filtration step at the same time has better practicality. Therefore, the present application proposes a new modified nanofiber membrane that can not only remove nickel ions, but also remove tin ions, that is, to achieve the simultaneous removal of nickel and tin from photovoltaic aluminum profile anodizing wastewater.

[0010] In order to achieve the above-mentioned purpose, the present application chemically modifies the polylactic acid electrospinning membrane by introducing a modifier into the spinning solution. The inventors have verified through a large number of experiments that three specific modifiers have the effect of simultaneously removing nickel and tin. The wastewater purification process based on the modified polylactic acid fiber membrane is simple to operate and saves labor costs, and has industrial promotion and application value.

[0011] The specific plan is as follows:

[0012] A method for preparing a modified nanofiber membrane comprises the following steps:

[0013] S1, dispersing polylactic acid in a solvent to obtain a dispersion;

[0014] S2, adding at least one modifier selected from niobium carbide, vanadium carbide and molybdenum carbide to the dispersion, stirring evenly to obtain a spinning solution;

[0015] S3, adding the spinning solution into an electrospinning device, and using the electrospinning device to perform spinning to obtain a modified nanofiber membrane.

[0016] Furthermore, the mass concentration of the dispersion is 1-15%, preferably 5-12%, and more preferably 8-10%. The concentration of the dispersion is controlled to control the electrostatic spinning process, thereby obtaining a spinning product with stable dimensions.

[0017] Furthermore, the mass ratio of the amount of the modifier added to the polylactic acid in the dispersion is 8-20 parts by weight: 80-92 parts by weight, preferably 10-18 parts by weight: 82-90 parts by weight, and more preferably 12-15 parts by weight: 85-88 parts by weight. The above-mentioned ratio of the modifier added can achieve satisfactory metal ion adsorption effect while meeting the mechanical performance requirements of the filter device for the nanofiber membrane used as a filter material.

[0018] Further, the modifier is preferably vanadium carbide, and preferably, the mass ratio of the addition amount of vanadium carbide to the polylactic acid in the dispersion is 13-15 parts by weight: 85-87 parts by weight. Different types of carbides have different adsorption effects on metal ions. The inventors found that compared with manganese carbide, niobium carbide, vanadium carbide, and molybdenum carbide have better nanofiber membrane modification effects, wherein the mass ratio of the addition amount of vanadium carbide to the polylactic acid in the dispersion is 13-15 parts by weight: 85-87 parts by weight, which can not only efficiently remove tin and nickel in wastewater, but also better maintain the original mechanical strength of the polylactic acid nanofiber membrane, avoiding the problem of a significant decrease in mechanical properties of other carbides.

[0019] Furthermore, the solvent is a mixture of dichloromethane and dimethylformamide, and the volume ratio of dichloromethane to dimethylformamide is 2-3:1.

[0020] The present invention also protects the modified nanofiber membrane prepared by the preparation method of the modified nanofiber membrane.

[0021] The present invention also protects a method for treating wastewater from anodizing of photovoltaic aluminum profiles containing nickel and tin, comprising passing the wastewater from anodizing of photovoltaic aluminum profiles containing nickel and tin through a filtering device, wherein the modified nanofiber membrane is installed in the filtering device.

[0022] Furthermore, the nickel concentration in the nickel-tin photovoltaic aluminum profile anodizing wastewater is 25-100 g / L, the tin concentration is 15-100 g / L, the wastewater pH is 1-6, and after being treated with the filtration device for 6-12 hours at room temperature, the nickel concentration in the wastewater does not exceed 0.5 g / L, and the tin concentration does not exceed 0.8 g / L.

[0023] Furthermore, the mass content of vanadium carbide in the modified nanofiber membrane is 13-15%, the removal rate of nickel in wastewater is greater than or equal to 99%, and the removal rate of tin in wastewater is greater than or equal to 98%.

[0024] Beneficial effects: The present invention provides a method for preparing a modified nanofiber membrane, which modifies the polylactic acid nanofiber membrane by using a two-dimensional transition metal carbide, thereby improving the metal ion removal efficiency of the fiber membrane.

[0025] Furthermore, the present invention improves the preparation method of the modified nanofiber membrane by adding at least one modifier selected from niobium carbide, vanadium carbide and molybdenum carbide to improve the simultaneous removal efficiency of nickel and tin.

[0026] Furthermore, the present invention optimizes the vanadium carbide loading of the modified nanofiber membrane and applies it to the treatment method of anodizing wastewater of photovoltaic aluminum profiles containing nickel and tin, so that the product has a nickel removal rate of greater than or equal to 99% and a tin removal rate of greater than or equal to 98% in the wastewater, has an excellent metal ion purification effect, and has prospects for industrial promotion and application. DETAILED DESCRIPTION

[0027] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, those without specifying specific techniques or conditions are carried out according to the techniques or conditions described in the literature in this area or according to the product specification. Those without specifying the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.

[0028] The test methods used below include:

[0029] Nickel and tin ions in water were detected by inductively coupled plasma optical electron spectroscopy (ICP-OES).

[0030] The main reagents used include:

[0031] Commercially available biodegradable polylactic acid (PLA): glass transition temperature: 65°C, degradation temperature range: 380°C-400°C, density 1.3g / L, heat deformation temperature 60°C. Obtained from: NatureWorks PLA4032D (polylactic acid for 3D printing)

[0032] The modifiers are two-dimensional transition metal carbides (2D TMCs): niobium carbide, vanadium carbide, molybdenum carbide, and manganese carbide, all of which are commercially available.

[0033] Solvent: DCM dichloromethane / DMF dimethylformamide, mixed volume ratio 2:1.

[0034] Examples 1-3

[0035] The preparation method of the modified nanofiber membrane, the amount of each raw material is shown in Table 1, comprises the following steps:

[0036] S1, dispersing polylactic acid in a solvent to obtain a dispersion;

[0037] S2, adding a modifier to the dispersion, stirring evenly, to obtain a spinning solution;

[0038] S3. Add the spinning solution into the electrospinning equipment, use the electrospinning equipment to perform spinning, select a spinning voltage of 12KV, a spray flow rate of 1.0ml / h, a receiving distance of 10cm, and use aluminum foil as a receiving plate. Dry the prepared nanofiber membrane at 50°C for 24 hours and take out the modified nanofiber membrane.

[0039] Table 1 Raw material dosage table / weight parts

[0040]

[0041] Example 4

[0042] Referring to Example 1, the modifier and dosage are different, the raw material dosage is shown in Table 1, and the preparation method is the same as Example 1.

[0043] Example 5

[0044] Referring to Example 1, the modifier and dosage are different, the raw material dosage is shown in Table 1, and the preparation method is the same as Example 1.

[0045] Example 6

[0046] Referring to Example 1, the modifier and dosage are different, the raw material dosage is shown in Table 1, and the preparation method is the same as Example 1.

[0047] Example 7

[0048] Referring to Example 1, the amount of raw materials used is the same as in Example 1, and the electrospinning process is different. The preparation method is as follows:

[0049] S1, dispersing polylactic acid in a solvent to obtain a dispersion;

[0050] S2, adding a modifier to the dispersion, stirring evenly, to obtain a spinning solution;

[0051] S3. Add the spinning solution into the electrospinning equipment, use the electrospinning equipment to perform spinning, select a spinning voltage of 10KV, a spray flow rate of 1.5ml / h, a receiving distance of 10cm, and use aluminum foil as a receiving plate. Dry the prepared nanofiber membrane at 50°C for 24 hours and take it out to obtain a modified nanofiber membrane.

[0052] Example 8

[0053] Referring to Example 1, the amount of raw materials used is the same as in Example 1, and the electrospinning process is different. The preparation method is as follows:

[0054] S1, dispersing polylactic acid in a solvent to obtain a dispersion;

[0055] S2, adding a modifier to the dispersion, stirring evenly, to obtain a spinning solution;

[0056] S3. Add the spinning solution into the electrospinning equipment, use the electrospinning equipment to perform spinning, select a spinning voltage of 13KV, a spray flow rate of 1.0ml / h, a receiving distance of 8cm, use aluminum foil as a receiving plate, dry the prepared nanofiber membrane at 50°C for 24 hours, and take out to obtain a modified nanofiber membrane.

[0057] Comparative Example 1

[0058] Referring to Example 1, manganese carbide is used as a modifier, the amounts of raw materials are shown in Table 1, and the preparation method is the same as Example 1.

[0059] Comparative Example 2

[0060] Referring to Example 1, pure polylactic acid was used to prepare an electrospinning membrane. The amounts of raw materials used were shown in Table 1. The preparation method was the same as in Example 1.

[0061] Nanofiber membrane performance test

[0062] The tests of tensile strength, Young's modulus and elongation at break were conducted according to ISO 527 test standard, and the instrument used was a universal material testing machine, model: INSTRON 5967; the test of flexural strength was conducted according to ISO 178 test standard, and the instrument used was a three-point bending tester, model: INSTRON 5582. The results are shown in the table below.

[0063] Table 2 Nanofiber membrane performance test results

[0064] project Tensile Strength Young's modulus Elongation at break Bending strength Example 1 20MPa 1.5GPa 7% 35MPa Example 2 20MPa 1.5GPa 7% 35MPa Example 3 20MPa 1.5GPa 7% 35MPa Example 4 25MPa 2GPa 6% 45MPa Example 5 30MPa 2.4GPa 4% 50MPa Example 6 33MPa 2.8GPa 3% 55MPa Example 7 20MPa 1.5GPa 6% 35MPa Example 8 20MPa 2GPa 4.5% 43MPa Comparative Example 1 20MPa 1.5GPa 7% 35MPa Comparative Example 2 5MPa 0.5GPa 10% 13MPa

[0065] As can be seen from Table 2, after adding 8% of two-dimensional metal carbide to Example 1, Example 2, Example 3, and Comparative Example 1, the mechanical properties of the nanofiber membrane are improved synchronously, because the two-dimensional metal carbide material has high strength, high conductivity and good dispersibility. In Example 4, Example 5, and Example 6, as the amount of two-dimensional metal carbide added gradually increases from 12% to 15%, the mechanical properties of the nanofiber membrane continue to improve, but the improvement gradually decreases, and even slightly decreases, especially the elongation at break, which is due to the interfacial bonding of the two-dimensional metal carbide during dispersion, resulting in partial agglomeration. While Example 7 and Example 8 changed the process parameters in Example 1, which affected the diameter of the electrospinning, the stretching effect, and the uniformity of the membrane. Although other parameters have been improved or maintained unchanged, the elongation at break has decreased. Therefore, the process parameters for preparing electrospinning nanofiber membranes need to be adjusted to the best effect and fixed.

[0066] Simulated sewage treatment experiment

[0067] The modified nanofiber membrane prepared in the above embodiments and comparative examples was used for sewage treatment. Simulated sewage was prepared, nickel sulfate and tin sulfate were added to deionized water and stirred evenly. The nickel ion concentration was 25 g / L and the tin ion concentration was 15 g / L. A small amount of dilute sulfuric acid was added to adjust the pH to 4.

[0068] The prepared modified nanofiber membrane was placed in a filter bag and put into a filter tank. Simulated sewage was introduced into the filter tank and adsorbed at room temperature for 10 hours. The ion concentration of the treated wastewater was then tested, as shown in Table 3 below.

[0069] Table 3 Sewage treatment experiment results

[0070] project Nickel content Tin content Example 1 0.42g / L 0.40g / L Example 2 0.41g / L 0.39g / L Example 3 0.32g / L 0.30g / L Example 4 0.31g / L 0.30g / L Example 5 0.15g / L 0.10g / L Example 6 0.09g / L 0.08g / L Comparative Example 1 10.90g / L 5.30g / L Comparative Example 2 19.50g / L 11.20g / L

[0071] As can be seen from Table 3, the pure polylactic acid nanofiber membrane in Comparative Example 2 has limited adsorption capacity for metal ions and cannot meet the requirements for wastewater discharge. After the polylactic acid is modified with manganese carbide in Comparative Example 1, the adsorption performance is not significantly improved; while niobium carbide, vanadium carbide, and molybdenum carbide have significant modification effects, showing good nickel and tin adsorption capacity, among which Example 3 is modified with vanadium carbide, and the adsorption performance is better than molybdenum carbide and niobium carbide; the vanadium carbide modified polylactic acid nanofiber membrane prepared in Examples 5 and 6 has a nickel removal rate of more than 99% in wastewater and a tin removal rate of more than 98% in wastewater, and has excellent application prospects.

[0072] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0073] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0074] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a modified nanofiber membrane, characterized in that: The following steps are involved: S1, dispersing polylactic acid in a solvent to obtain a dispersion; S2, adding at least one modifier selected from niobium carbide, vanadium carbide and molybdenum carbide to the dispersion, stirring evenly to obtain a spinning solution; S3, adding the spinning solution into an electrospinning device, and using the electrospinning device to perform spinning to obtain a modified nanofiber membrane.

2. The method for preparing the modified nanofiber membrane according to claim 1, characterized in that: The mass concentration of the dispersion is 1-15%, preferably 5-12%, and more preferably 8-10%.

3. The method for preparing the modified nanofiber membrane according to claim 2, characterized in that: The mass ratio of the added amount of the modifier to the polylactic acid in the dispersion is 8-20 parts by weight: 80-92 parts by weight, preferably 10-18 parts by weight: 82-90 parts by weight, and more preferably 12-15 parts by weight: 85-88 parts by weight.

4. The method for preparing the modified nanofiber membrane according to claim 3, characterized in that: The modifier is preferably vanadium carbide. Preferably, the mass ratio of the added amount of vanadium carbide to the polylactic acid in the dispersion is 13-15 parts by weight: 85-87 parts by weight.

5. The method for preparing the modified nanofiber membrane according to any one of claims 1 to 4, characterized in that: The solvent is a mixed solution of dichloromethane and dimethylformamide, and the volume ratio of dichloromethane to dimethylformamide is 2-3:

1.

6. The modified nanofiber membrane prepared by the method for preparing the modified nanofiber membrane according to any one of claims 1 to 5.

7. A method for treating wastewater from anodizing of photovoltaic aluminum profiles containing nickel and tin, characterized in that: The photovoltaic aluminum profile anodizing wastewater containing nickel and tin is passed through a filtering device in which the modified nanofiber membrane according to claim 6 is installed.

8. The method for treating the nickel-tin photovoltaic aluminum profile anodizing wastewater according to claim 7, characterized in that: The nickel concentration in the nickel-tin photovoltaic aluminum profile anodizing wastewater is 25-100 g / L, the tin concentration is 15-100 g / L, the pH value of the wastewater is 1-6, and after being treated with the filtering device for 6-12 hours at room temperature, the nickel concentration in the wastewater does not exceed 0.5 g / L, and the tin concentration does not exceed 0.8 g / L.

9. The method for treating nickel-tin photovoltaic aluminum profile anodizing wastewater according to claim 8, characterized in that: The mass content of vanadium carbide in the modified nanofiber membrane is 13-15%, the removal rate of nickel in waste water is greater than or equal to 99%, and the removal rate of tin in waste water is greater than or equal to 98%.

Citation Information

Patent Citations

  • Preparation method of nano-fiber membrane for adsorbing heavy metal nickel ions in wastewater

    CN109107549A

  • Two-dimensional titanium carbide adsorbent and application thereof

    CN108273469A

  • Functionalized nano-fiber filter material and preparation method and application thereof

    CN108579212A

  • Preparation method and application of supported transition metal carbide Fenton-like nano-catalyst

    CN111715250A

  • MXene and bamboo fiber assembly as well as preparation method and application thereof

    CN115286060A